2023
DOI: 10.1097/md.0000000000033926
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality and related influencing factors in adult hypertensive patients in Shandong Province, China

Abstract: Hypertension is a leading cause of death worldwide. Hypertension is associated with poor sleep quality, which adversely affects physical and mental health, and can increase the incidence rate and mortality of cardiovascular disease, cancer, and depression. This study aimed to investigate the prevalence of the factors related to poor sleep quality in hypertensive patients in Shandong Province, China. This cross-sectional study of adult patients with hypertension from August 2020 to February 2021was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“… 17 21 It was however similar to the finding in a cross-sectional, hospital-based study among hypertensive adults within an urban China Province where a prevalence of 60.4% was reported. 22 The similarities in the prevalence in rural and urban settings can be attributed to the referral nature of these centres. This high prevalence has important implications regarding blood pressure control and the increasing morbidity from cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“… 17 21 It was however similar to the finding in a cross-sectional, hospital-based study among hypertensive adults within an urban China Province where a prevalence of 60.4% was reported. 22 The similarities in the prevalence in rural and urban settings can be attributed to the referral nature of these centres. This high prevalence has important implications regarding blood pressure control and the increasing morbidity from cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Sayorwan et al (2012) found that lavender aromatherapy can increase alpha brain waves (8-13 Hz) associated with decreased stress and theta waves (4-8Hz), thereby improving sleep quality. Overcoming stress and improving sleep quality are important components of hypertension control (Bautista et al, 2019;Birhanu et al, 2021;Gou et al, 2023).…”
Section: Introductionmentioning
confidence: 99%